Reading attitudes among faculty of information management students at UiTM Puncak Perdana Campus / Siti Nor Faezah Ahmad - Ahmad, Siti Nor Faezah (Faculty of Information Management, 2009)
What are the reading habits of Malaysian students at the university? Will efficient readers achieve higher levels of academic achievement? How do our students perceive their reading ability? How much do Malaysians read? According to the last National Literacy Survey carried out in 1996 by the National Library, the average Malaysian reads only two books a year! This is an improvement compared to an earlier survey in 1982 which revealed that an average Malaysian read a mere page or two a year. The Sunday Star newspaper (8th August, 1999:p2) reports that "the poor reading habits among Malaysians was common knowledge but, in true Malaysian fashion, it took an official survey to jolt the education sector that something had to be done fast." According to Sarjit (1999) the studies in the past have shown that the examoriented educational system in Malaysia promotes learning and that needs to be a paradigm shift in how we view education and about the way we teach. The Education Minster, Datuk Najib Tun Razak, has frequently commented in the local media that most students read only to pass exams and do not read for pleasure. He has been instrumental in implementing many projects aimed at improving students' reading ability in the country. Reading skills are important through out our lifetime, particularly as we respond to new demands and changes in jobs and reading for pleasure or recreational has been found to improve reading comprehension, writing style, vocabulary, spelling and grammatical development.Over the past twenty years, increasing numbers of Malaysians have enrolled in institutions of higher learning in the country. Admission decisions are usually made on the basis of the applicants' academic performance in standardized